Capturing the value creation in public procurement: A practice-based view. Issue 2 (March 2022) - Malacina, Iryna; Karttunen, Elina; Jääskeläinen, Aki; Lintukangas, Katrina; Heikkilä, Jussi; Kähkönen, Anni-Kaisa
Abstract: Public procurement has struggled to fulfill its mission to create public value due to a narrow interpretation of value emphasizing the costs of procured goods and services. A holistic view of multidimensional value creation in the context of public procurement has received limited research attention despite a significant body of research on the potential benefits associated with public procurement. The purpose of this paper is to fill this gap by analyzing the value components and means of value creation developed through public procurement activities. We conduct a systematic literature review and content analysis of 171 research articles to determine the constituents of the value of public procurement and the practices needed to achieve them. Using the theoretical lens of the practice-based view, we propose a conceptual framework that holistically integrates different components of the value of public procurement for the public buyer, supplier, and user, along with the practices needed to achieve them. The study contributes to the literature by offering a multidimensional conceptual framework, a structured review of value components and associated practices, and the application of the practice-based view as the theoretical lens, all of which have implications for practice and theory.